COMORBIDITIES OF MYASTHENIC CRISIS PATIENTS ACCORDING TO AGE AND GENDER IN DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA IN 2017-2019 - Andi Muh Rahul Alfaidin; Viskasari P Kalanjati; Mudjiani Basuki (Universitas Airlangga, Surabaya, Indonesia, 2022)
Highlight:1. Patients with myasthenia gravis (MG) can have both autoimmune and non-autoimmune comorbidities.2. MG patients were predominantly aged >50 years, females and the commonest comorbidity are hypertension and diabetes mellitus.3. Age and comorbidities were found to have significant correlation among these patients, but not between gender and comorbidities.Abstract:Background: There are limited studies on the comorbidities of myasthenic crisis (MC) associated with age and gender, specifically from Indonesia. These data might be valuable for treatment to improve the outcome of these patients. Objective: To analyze the correlation between age and gender with the comorbidities amongst the MC patients admitted in the ICU of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia in 2017-2019. Materials and methods: A retrospective cross-sectional analytic study was conducted on 25 medical records of MC patients who fulfilled the inclusion and exclusion study criteria. Descriptive statistics and Chi-square tests were done to determine the potential correlation between variables (significant level of p<0.05). Results: The age of MC patients was £50 years (80%) and >50 years (20%) while the gender predominantly found were females (68%) with 32% males. A significant correlation was found between age and comorbidities (p=0.002) whilst not between gender and comorbidities (p=0.115). The most common comorbidities observed were hypertension (30%) and diabetes mellitus (20%). Conclusion: There were 40% of patients found with comorbidities. There was a significant association between age and comorbidities found amongst myasthenic crisis patients, whilst no significant association was found between gender and comorbidities.